Back Cover: Water‐Based Synthesis of Zeolitic Imidazolate Framework‐90 (ZIF‐90) with a Controllable Particle Size (Chem. Eur. J. 34/2013). Issue 34 (14th August 2013) - Shieh, Fa‐Kuen; Wang, Shao‐Chun; Leo, Sin‐Yen; Wu, Kevin C.‐W.
<x xml:space="preserve">Abstract</x> Water‐based, environmentally friendly, size controllable and rapid synthesis of zeolitic imidazolate framework‐90 nanoparticles (ZIF‐90 NPs) is described. In their Communication on page 11139 ff., F.‐K. Shieh, Kevin C.‐W. Wu et al. report the synthesis of ZIF‐90 NPs with the smallest particle size of 270 nm in a water‐based (H2O/alcohol/PVP) system under ambient conditions. The effects of PVP polymer concentration, alcohol, and Zn/ICA ratio on the properties of these NPs were also investigated. The image of Taiwan (home country of the authors, depicted in the first sphere) was provided from CSRSR at National Central University, and the Cover picture was made by Professor C.‐K. (Frank) Tsung in Boston College.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>